2020
DOI: 10.3390/ijms21124332
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Cell Proliferation in Secondary Hyperparathyroidism of Chronic Kidney Disease

Abstract: Secondary hyperparathyroidism (SHP) is a common complication of chronic kidney disease (CKD) that correlates with morbidity and mortality in uremic patients. It is characterized by high serum parathyroid hormone (PTH) levels and impaired bone and mineral metabolism. The main mechanisms underlying SHP are increased PTH biosynthesis and secretion as well as increased glandular mass. The mechanisms leading to parathyroid cell proliferation in SHP are not fully understood. Reduced expressions of the receptors for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 112 publications
(136 reference statements)
1
12
0
4
Order By: Relevance
“…These results highlight the essential role of mTORC1 activation by rpS6 phosphorylation in parathyroid cell proliferation and in the pathogenesis of SHP. EGFR activates the AKT-mTORC1 pathway; therefore, the mTORC1 and EGFR pathways may act together to stimulate parathyroid cell proliferation in SHP [99] (Figure 3).…”
Section: The Mtorc1 Pathwaymentioning
confidence: 99%
“…These results highlight the essential role of mTORC1 activation by rpS6 phosphorylation in parathyroid cell proliferation and in the pathogenesis of SHP. EGFR activates the AKT-mTORC1 pathway; therefore, the mTORC1 and EGFR pathways may act together to stimulate parathyroid cell proliferation in SHP [99] (Figure 3).…”
Section: The Mtorc1 Pathwaymentioning
confidence: 99%
“…Several epidemiological studies report an association between plasma phosphate and increased cardiovascular disease and mortality in dialysis and pre-dialysis CKD population as well as in the general population [56][57][58][59][60][61]. The observational studies are also backed up by experimental studies illustrating a negative impact on the organism by phosphate overload [62][63][64][65][66][67]. More specifically, Li et al showed in in vitro studies that extracellular phosphate uptake via the type III sodium phosphate co-transporter (Pit1) induced the change in the phenotype of VSMC to a bone-like cell.…”
Section: Dramatic Changes In the Vasculature In Ckdmentioning
confidence: 99%
“…Furthermore, the binding of vitamin D to VDR of the parathyroid gland inhibits PTH synthesis, which constitutes an important feedback mechanism related to Ca 2+ homeostasis ( Navarro-García et al, 2018 ). The loss of renal function is frequently related to vitamin D deficiency ( Wolf, 2010 ) and increased synthesis of PTH (secondary hyperparathyroidism) ( Madsen et al, 1981 ; Naveh-Many and Volovelsky, 2020 ).…”
Section: Mineral Bone Disorders and Cardiorenal Syndromementioning
confidence: 99%